Concept and Features of Legal Regime of Land for Domestic Waste Landfills - Tetyana Kovalchuk (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The article is devoted to the concept and legal features of legal regime of solid domestic waste landfills, including legal relationship in the field of land remediation of solid domestic waste landfills after their termination. Basing on analysis of the special literature and the current legislation of Ukraine it is proposed to make amendments to the current Land Code of Ukraine, which enables to realize the goals and tasks of the modern state, regional, local, and objective environmental policy in practice.